2020
DOI: 10.1097/ico.0000000000002356
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye and Quantitative and Qualitative Changes of Meibomian Glands in Patients With Pemphigus

Abstract: Purpose: To evaluate dry eye and quantitative and qualitative changes of meibomian glands with meibography in patients with pemphigus. Methods: Twenty left eyes of 20 patients with pemphigus (group 1) and 20 left eyes of 20 age- and sex-matched healthy volunteers (group 2) were enrolled. Dry eye was evaluated with Oxford scale scoring, tear film breakup time, Schirmer 1 tests, and Ocular Surface Disease Index score assessments. Morphological changes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The meibomian gland plays a vital role in maintaining the stability of tear film, and an increased meiboscore is generally considered as the important risk factor for DED and contact lens-related discomfort ( 37 , 38 ). Previous studies have examined the influence of OOK wearing on the morphology of the meibomian gland based on non-contact infrared meibography or Keratograph 5M and found that there is no significant difference in the meiboscore before and after wearing lenses ( 12 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The meibomian gland plays a vital role in maintaining the stability of tear film, and an increased meiboscore is generally considered as the important risk factor for DED and contact lens-related discomfort ( 37 , 38 ). Previous studies have examined the influence of OOK wearing on the morphology of the meibomian gland based on non-contact infrared meibography or Keratograph 5M and found that there is no significant difference in the meiboscore before and after wearing lenses ( 12 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies that mention the link between inflammatory dermatological diseases like vitiligo, 31 pemphigus, 32 dry eye, and Meibomian gland dysfunction. Other non-invasive imaging tools and procedures have been used in ocular sarcoidosis such as conjunctiva's in vivo confocal microscopy for identifying multinucleated giant cells in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The natural eye-blinking motion recurrently irrigates the surface of the eye using eye-tear uid and lubricant oil (produced by the Meibomian glands [24][25][26] ) thus refreshing the uid in contact with the electrodes. As a result of the eyelid motion, the electrodes essentially remain under one of three conditions: (a) fully covered by the eye-tear uid (completely shut eyelid), (b) partially covered by the eyetear (during the cycle of an eye-blink) or (c) not in contact with the eye-tear (when the eyelid is completely open).…”
Section: Experimental Methodsmentioning
confidence: 99%